Efektifitas Pelatihan Kader terhadap Peningkatan Kompetensi Kader dalam Pemberian Pelayanan Kesehatan Ibu dan Anak - Isir, Mariana; Duhita, Fitra (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2025)
Background: Acceleration of the Health System Transformation achievement program in the first pillar, namely Primary Service Transformation, reconstruction of primary health services was carried out by making Cadres one of the human resources implementing it. The purpose of this study was to determine the effectiveness of cadre training on improving cadre competence in providing counseling to pregnant women. Method: This study is a quantitative descriptive pre-experimental study with a pretest-posttest design. The sample in this study were 29 Posyandu Cadres responsible for examining pregnant women in all Posyandus in the Malawili Health Center working area. The intervention given was cadre training to provide counseling to pregnant women. Pretest-posttest data are the results of observations of cadre competence in conducting counseling using an instrument in the form of a checklist. Result: The results of the analysis showed that there was a significant difference between the pretest and posttest values ​​in all aspects (p-value <0.05). Further calculation results on the effectiveness of providing training on improving cadre competence showed that the training provided was low (N-Gain score 0.23 <0.3). Implication: This study is expected to provide an overview of the readiness and preparation for cadres, especially in the work area of ​​the Malawili Health Center, Sorong Regency, to implement several parts of the 25 cadre competencies. Novelty: This study focuses on assessing cadre competency based on the performance of knowledge, attitude and skills in providing counseling to pregnant women.